Digital Texts in Practice - Christian Wittern (Journal of the Text Encoding Initiative)
As a student of intellectual, religious, and cultural developments in areas of the Chinese cultural sphere, my initial motivation for engaging with digital texts thirty years ago was to open up the new possibilities that the digital medium offered to researchers, without losing any of the affordances of a traditional printed edition. This requirement includes use of texts for reading, translating, annotating, quoting, and publishing, thus integrating with the whole of the scholarly workflow. At that time theories of electronic texts started to appear and the Text Encoding Initiative had already begun to create a common text model and interchange specification, based mainly on European languages. For East Asian texts, things were much more complicated because of different and quickly evolving character encoding standards, different textual traditions and approaches to text editing, as well as different institutional embedding. In this paper, I will look back at these developments, first to recount some of the history, albeit from a strictly personal perspective, but also to take stock of the situation and consider where we are now, how we got there, and what remains to be done to realize the dream of the universal digital text, easily shared and annotated, but still tractable, verifiable, and authoritative.